2016
DOI: 10.21707/gs.v10.n04a21
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes e crescimento de Ormosia arborea em diferentes temperaturas e substratos

Abstract: -Olho-de-cabra species belonging to the Fabaceae family, distributed through of Atlantic rain forest and semideciduous stationary forest. Its wood is suitable for manufacture of furniture and tree recommended for urban forestry and also considered medicinal. Taking into account their potential use this work was developed with the objective of evaluates the effect of different temperatures and substrates on the germination rate and initial root growth. The seeds used in this experiment were collected in the Sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…This temperature range is the same as that of the environment where seeds were collected. Oliveira et al (2016) verified GSI values of Ormosia arborea seeds similar to those of the present study. According to the authors, 25-35 °C is the optimal germination temperature range for the species.…”
Section: Resultssupporting
confidence: 92%
“…This temperature range is the same as that of the environment where seeds were collected. Oliveira et al (2016) verified GSI values of Ormosia arborea seeds similar to those of the present study. According to the authors, 25-35 °C is the optimal germination temperature range for the species.…”
Section: Resultssupporting
confidence: 92%
“…Evaluating seed germination of Ormosia arborea (Vell.) Harms, Oliveira et al (2016) indicated that the tested lower temperature, 20 °C, affected negatively the germination process, in correlation with the seeds kinetic energy decrease, a result similar to that found by this work.…”
Section: Discussionsupporting
confidence: 88%
“…The lowest Mean germination time for seed germination occurred at 30 o C in the presence of light, while for the absence of light, the lowest mean germination time occurred at 25, 30, 35, and 20-30 o C. The temperatures of 25, 30, and 20-30 o C promoted faster germination speeds both in the absence and presence of light (Figure 1). In another study with the same species, the authors indicated the temperature of 30 o C as the best for seed germination on the substrate containing sand (Oliveira et al, 2016). O. arborea seeds require a long period to germinate, as do many native species.…”
Section: Resultsmentioning
confidence: 97%